2019
DOI: 10.3389/fcell.2019.00023
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Roles of Cell Cycle Regulators

Abstract: Core cell cycle regulators, including cyclin-dependent kinases (CDKs), cyclins, and cyclin-dependent kinase inhibitors (CKIs), are known for their well-characterized roles in cell division. Several recent studies have shed light on the roles of these proteins in immune modulation. The development and activation of cells in the immune system take place not only during embryonic development but throughout the life of a multicellular organism. Cell cycle regulators are involved in the development of immune cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
0
40
0
3
Order By: Relevance
“…Although the literature of CDK2 in the context of innate immunity and inflammation is scarce (as reviewed in ref. 57), CDK2 possibly regulates the secretion of inflammatory cytokines in macrophages. In addition, a single-nucleotide polymorphism of CDK2 is significantly enriched in asthma patients (58), supporting the possible function of CDK2 in regulating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature of CDK2 in the context of innate immunity and inflammation is scarce (as reviewed in ref. 57), CDK2 possibly regulates the secretion of inflammatory cytokines in macrophages. In addition, a single-nucleotide polymorphism of CDK2 is significantly enriched in asthma patients (58), supporting the possible function of CDK2 in regulating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Another defined mechanisms by which L-arg starvation restricts T-cells activation and proliferation is the regulation of cell cycle progression (232) via modulation of cyclin D3 mRNA stability (240). Cyclins, including cyclin D3 (241), are critical regulators of the cell cycle, immune cells development and proliferation (242). L-arg starvation arrests human T-cells in G 0 -G 1 phase (232).…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
“…CDK4/6 inhibitors could repress immunosuppressive regulatory T cells (Tregs) and enhance effector T cells response by upregulating the level of cytokines (IL-2) in the tumor microenvironment [94]. Cyclin D-CDK4 complex was also reported to play a role in reducing the expression of PD-L1; therefore CDK4/6 inhibitors could promote expression of PD-L1, causing tumor immune evasion [95,96]. These findings suggested that CDK4/6 inhibitors showed combinatorial benefit when combined with anti-PD-L1 therapy.…”
Section: Biological Rationale For Novel Combination Strategiesmentioning
confidence: 99%